Nuestras aves perdidas - González Táboas, FRANCISCO; BONANNO, JUAN JOSÉ; DI GIACOMO, ALEJANDRO (Revista Aves Argentinas, 2026)
Accedé al artículo ingresando a la revista (hacé click sobre la portada y/o el número).